Metagenomics Analysis of the Microbial Consortium in Samples from Lake Xochimilco, a World Cultural Heritage Site - Alvaro de Obeso Fernández del Valle; Jorge Membrillo-Hernández (Microorganisms)
Since ancient times, the community of Xochimilco in the south of Mexico City has provided vegetables for the entire city. Today, Lake Xochimilco is listed as a UNESCO World Heritage Site because it is the last remaining bastion of Aztec culture and preserves the extraordinary ecological landscape of chinampas, a system of arable islands that has endured for over 1000 years. Here, we report on the microbiological communities currently existing in the lake. This is relevant since the water irrigates crops on the islands, known as chinampas. To achieve this, samples from the lake were collected at two different sites, and metagenomics analysis of the 16S gene was conducted. The results indicate the presence of five dominant bacterial phyla: Actinobacteria (44.5%), Proteobacteria (22.5%), Firmicutes (13%), Bacteroidota (6%), and Chloroflexi (4.6%). The most abundant families were Micrococcaceae, Intrasporangiaceae, and Rhodobacteraceae. The results correlate with current anthropogenic activity, indicating a moderate problem associated with contamination. Our findings suggest that immediate actions and increased awareness are necessary to preserve this cultural and natural heritage site and to take steps to comply with Sustainable Development Goal 11 (Sustainable Cities and Communities). Furthermore, this is the first report to characterize microbial communities in the water of Lake Xochimilco using 16S rRNA gene sequencing.